Exploring the biophysical option space for feeding the world without deforestation - Karl-Heinz Erb (Nature Portfolio, 2016)
Safeguarding existing forests is an important ecological concern but constrains the expansion of farmland to feed the growing world population. Here the authors analyse the option space for future changes in agriculture and diets compatible with a no-deforestation goal.